Lactobacillus plantarum Alleviates Obesity by Altering the Composition of the Gut Microbiota in High-Fat Diet-Fed Mice - Ma, Yong; Fei, Yanquan; Han, Xuebing; Liu, Gang; Fang, Jun (Frontiers in Nutrition, 2022)
Metabolic disorders and intestinal flora imbalance usually accompany obesity. Due to its diverse biological activities, Lactobacillus plantarum is widely used to alleviate various diseases as a probiotic. Here, we show that L. plantarum can reduce the body weight of mice fed high-fat diets, reduce fat accumulation, and enhance mice glucose tolerance. Our results show that L. plantarum can significantly reduce the expression of DGAT1 and DGAT2, increase the expression of Cpt1a, and promote the process of lipid metabolism. Further data show that L. plantarum can increase the SCFA content in the colon and reverse the intestinal flora disorder caused by HFD, increase the abundance of Bacteroides, and Bifidobacteriales, and reduce the abundance of Firmicutes and Clostridiales. Finally, through Pearson correlation analysis, we found that Bacteroides and SCFAs are positively correlated, while Clostridiales are negatively correlated with SCFAs. Therefore, we believe that L. plantarum can regulate the structure of the intestinal microbial community, increase the production of SCFAs and thus regulate lipid metabolism.